Impact of end‐diastolic and end‐systolic phase selection in the volumetric evaluation of cardiac MRI. Issue 3 (2nd September 2015) - Contijoch, Francisco; Witschey, Walter R.T.; Rogers, Kelly; Gorman, Joseph; Gorman, Robert C.; Ferrari, Victor; Han, Yuchi
Abstract : Purpose: To evaluate the impact of end‐diastolic (ED) and end‐systolic (ES) cardiac phase selection methods, since task force recommendations have neither provided quantitative evidence nor explored errors introduced by clinical shortcuts. Materials and Methods: Multislice, short‐axis cine images were collected in 60 clinical patients on a 1.5T scanner. User‐initialized active contour segmentation software quantified global left ventricular (LV) volume across all cardiac phases. Different approaches for selection of ED and ES phase were evaluated by quantification of temporal and volumetric errors. Results: For diastole, the mid‐ventricular maximum slice volume coincided with maximum global volume in 82.1% of patients with ejection fraction (EF) ≥55% ( P  = 0.66) and 71.9% of patients with EF <55% ( P  = 0.28) and is an accurate approximation of maximum global volume while the first and last phases in a retrospectively electrocardiogram (ECG)‐gated acquisition introduced differences in cardiac phase selection ( P < 0.001) which led to large errors in measured volume in some patients (12.7 and 10.1 mL, respectively). For systole, post‐systolic shortening occurred in a significantly higher number of patients with EF <55% (18.9%) compared to 3.6% of patients with EF ≥55% ( P  = 0.001), which differentially impacted end‐systolic volume estimation. Conclusion: For end‐diastolic phase selection, our results indicated that the use of the mid‐ventricular slice volume maximum provided accurate volume estimates, while selection of the first or last cardiac phase introduced differences in measured volume. For end‐systolic phase, patients with EF <55% had a higher prevalence of post‐systolic shortening, which suggests aortic valve closure should be used to estimate end‐systolic volume. J. MAGN. RESON. IMAGING 2016;43:585–593.